Motu Proprio «Crebrae allatae sunt» on the Discipline of Sacramenti Matrimonii pro Ecclesia Orientali - Pujol, Clemente (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2023)
The significant words «Crebrae allatae sunt» mark the beginning of the motu proprio through which Pope Pius XII promulgated a part of the already codified Eastern Canon Law, specifically all canons related to marriage. As the Holy Father himself noted, these words are a prelude to broader future developments, and their importance is evident not only in the history of Canon Law in general but also, particularly, in Eastern Canon Law and even in the history of sister churches in the East.
Keywords: Crebrae allatae sunt; marriage; eastern Church; sacraments; motu proprio